2023
DOI: 10.1021/acscatal.3c00755
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Improved Catalytic Dehydration of Sorbitol to Isosorbide by Sol–Gel Sulfated Zirconia: A Quantitative Structure–Reactivity Study

Abstract: Isosorbide, a bicyclic C6 diol, has considerable value as a precursor for the production of bio-derived polymers. Current production of isosorbide from sorbitol utilizes homogeneous acid, commonly H2SO4, creating harmful waste and complicating separation. Thus, a heterogeneous acid catalyst capable of producing isosorbide from sorbitol in high yield under mild conditions would be desirable. Reported here is a quantitative investigation of the liquid-phase dehydration of neat sorbitol over sulfated zirconia (SZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…27–30 Hopper et al found that the metal sulfates of Zr, Sn, Ti, and Cu also had suitable Brønsted acid sites for sorbitol dehydration, and isosorbide yields of 61% to 76% could be obtained. 31–35 According to these catalysts reported in previous papers, it can be seen that acidic resins, commercial resins, and self-prepared sulfonated polystyrene resins exhibited much higher activity, selectivity, and stability for sorbitol dehydration to isosorbide when compared to other heterogenous catalysts due to their high Brønsted acid strength and large quantity of sulfonate groups in aromatic rings.…”
Section: Introductionmentioning
confidence: 87%
“…27–30 Hopper et al found that the metal sulfates of Zr, Sn, Ti, and Cu also had suitable Brønsted acid sites for sorbitol dehydration, and isosorbide yields of 61% to 76% could be obtained. 31–35 According to these catalysts reported in previous papers, it can be seen that acidic resins, commercial resins, and self-prepared sulfonated polystyrene resins exhibited much higher activity, selectivity, and stability for sorbitol dehydration to isosorbide when compared to other heterogenous catalysts due to their high Brønsted acid strength and large quantity of sulfonate groups in aromatic rings.…”
Section: Introductionmentioning
confidence: 87%